Comparative study of conventional and micro WEDM based on machining of meso/micro sized spur gear - Ali, Mohammad Yeakub; Karim, A.N. Mustafizul; Adesta, Erry Yulian Triblas; Ismail, Ahmad Faris; Abdullah, 'Aisy Anuarin; Idris, Mohd Nazrol (Springer, 2010)
This paper discusses the comparison of micro machining process using conventional and micro wire electrical discharge machining (WEDM) for fabrication of miniaturized components. Seventeen toothed miniaturized spur gear of 3.5 and 1.2 mm outside diameter were fabricated by conventional and micro WEDM respectively. The process parameters for both conventional and micro WEDM were optimized by preliminary experiments and analysis. The gears were investigated for the quality of surface finish and dimensional accuracy which were used as the criteria for the process evaluation. An average surface roughness (Ra ) of 50 nm and dimensional accuracy of 0.1-1 μm were achieved in micro WEDM. Whenever applied conventional WEDM for meso/micro fabrication, a Ra surface roughness of 1.8 μm and dimensional accuracy of 2-3 μm were achieved. However, this level of surface roughness and dimensional accuracy are acceptable in many applications of micro engineering. A window of conventional WEDM consisting of low energy discharge parameters is identified for micromachining.